Constructing landscape : materials, techniques, structural components - Zimmermann, Astrid, 1967- (Base, Switzerland : Birkhauser Verlag, 2011)
This is a systematic introduction to technical and constructional open space planning, with all the relevant topics covered, from the most common materials and surfaces to the construction of open space elements and the use of plants. The text is supported by over 1200 photographs, illustrations and plans.
Keywords: Landscape architecture -- Design and construction; Landscape architecture -- Technique